1998
DOI: 10.1016/s0378-4274(98)00126-x
|View full text |Cite
|
Sign up to set email alerts
|

Thallium toxicity

Abstract: Thallium (T1+) is a toxic heavy metal which was accidentally discovered by Sir William Crookes in 1861 by burning the dust from a sulfuric acid industrial plant. He observed a bright green spectral band that quickly disappeared. Crookes named the new element 'Thallium' (after thallos meaning young shoot). In 1862, Lamy described the same spectral line and studied both the physical and chemical properties of this new element (Prick, J.J.G., 1979. Thallium poisoning. In: Vinkrn, P.J., Bruyn, G.W. (Eds.), Intoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
160
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(167 citation statements)
references
References 51 publications
2
160
0
5
Order By: Relevance
“…Two scientists, William Crookes and ClaudeAuguste Lamy independently discovered thallium by fl ame spectroscopy (11). At that time, this was a new improved method to make spectroscopic determinations of minerals.…”
Section: Physical and Chemical Properties Of Thalliummentioning
confidence: 99%
See 2 more Smart Citations
“…Two scientists, William Crookes and ClaudeAuguste Lamy independently discovered thallium by fl ame spectroscopy (11). At that time, this was a new improved method to make spectroscopic determinations of minerals.…”
Section: Physical and Chemical Properties Of Thalliummentioning
confidence: 99%
“…An exception are underdeveloped countries where thallium is still in use. The WHO recommendation against its use dates from 1973 (27).…”
Section: Usesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thallium appears in two oxidation states; Tl (І) which is highly soluble in aqueous environments and resembles alkali metals and Tl (III) which is more stable forming complexes with sulphates, chlorides, carbonates and nitrates [5][6][7]. Thallium deposits are generally scarcely distributed worldwide with many industrial applications such as catalyst for making certain alloys, molecular probes, thermometers, acusto-optical equipment, optical glass with refractive index, imitation jewellery, scintillation counters, and super-conductivity in ceramic compounds [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Part of the reason for thallium's high toxicity is that Tl + shares similarities in ionic charge and crystal radius with K + ; it can thus occupy certain K + binding sites, and it can also interact with sulfydryl groups at the mitochondrial membrane. 10 Recently it has been found that Tl 3+ interferes with glutathione metabolism 11 and alters the physical properties of the liposome membrane, following the order Tl…”
Section: Introductionmentioning
confidence: 99%